The Effect of Leadership Style and Compensation on Employee Performance Mediated by Work Motivation at PT. Alrazaak Abadi Mandiri in Makassar - Muhammad Yasser; Nurdin Brasit; Maat Pono (STIE AMKOP, 2023)
This research was conducted at PT Alrazaak Abadi Mandiri Makassar. At the same time, the time required during the research takes approximately three months, from August 2022 to October 2022. In this study, the authors made PT Alrazaak Abadi Mandiri Makassar employees the population. The type of sample used is a saturated sample because the population in this study was 46 employees. Hence, the number of samples was the same as the population. Based on the research and discussion results, it concludes that leadership style does not significantly affect work motivation at PT Alrazaak Abadi Mandiri Makassar. This means that even though the better the leadership style, it will not affect employee work motivation. Compensation has a significant effect on work motivation at PT. Alrazaak Abadi Mandiri Makassar. This means that the better the compensation employees obtain, the more employee work motivation will increase. Leadership style has no significant effect on performance at PT. Alrazaak Abadi Mandiri Makassar. This means that even though the better the leadership style, it will not affect employee performance. Compensation has a significant effect on performance at PT. Alrazaak Abadi Mandiri Makassar. This means that the better the compensation employees obtain, the more employee performance will increase. Work motivation has a significant effect on performance at PT. Alrazaak Abadi Mandiri Makassar. This means that the higher the employee's work motivation, the more employee performance will increase. Indirectly leadership style through work motivation significantly affects performance at PT. Alrazaak Abadi Mandiri Makassar. This means that the better the leadership style, the more employee work motivation and performance will increase. Indirectly compensation through work motivation does not significantly affect performance at PT Alrazaak Abadi Mandiri Makassar. This means that even though the better the compensation obtained by employees, it will not affect work motivation and performance. Keywords: Leadership, compensation, performance, work motivation